MO075: Decline of Regenerative Capacity of Renal Progenitors and Progressive Polyploidization of Tubular Cells Contribute to Kidney Physiologic Response During Aging. (3rd May 2022) - Antonelli, Giulia; Conte, Carolina; De Chiara, Letizia; , Lazzeri; Romagnani, Paola
Abstract: BACKGROUND: The biological process of renal aging is characterized by progressive structural and functional deterioration of the kidney leading to end-stage renal disease in elderly patients. Renal aging includes a complex network of cellular signaling stress such as senescence, mitochondrial dysfunction, autophagy and DNA damage repair. In organs with high turnover rate, aging is frequently accompanied by an impairment of progenitor cell proliferation. In organs with low turnover rate, such as the kidney, aging is likely associated with additional strategies to maintain homeostasis. Recently, we provided groundbreaking evidence that the kidney responds to injury by triggering two mechanisms: (i) the proliferation of renal progenitors (Pax2 + cells, RPC) which represent a subset of self-renewing cells able to regenerate lost kidney cells, and (ii) the polyploidization of renal tubular epithelial cells (TEC), which allows to increase the cell DNA content without passing mitosis, generating mononuclated/polinucleated cells. Physiologically, polyploidy offers several advantages such as rapid adaptation to stress, compensation for cell loss and enhanced cell function to support augmented functional demand. We hypothesized that an impaired regenerative capacity and progressive TEC polyploidization are involved in the kidney physiologic response during aging. METHODS: To test whether the proliferation of RPC (Pax2 + cells) contribute to tubular turnover during aging, we took advantage of Pax2.rtTA; tetO.cre; R26.Confetti mouse model for lineage tracing of RPC during their life span at different time points (8, 20, 44 and 80 weeks). To evaluate the presence and accumulation of polyploid TEC during aging, we took advantage of the Pax8.rtTA; tetO.cre; R26.FUCCI2aR conditional mouse model, at different ages (8, 20, 44 and 80 weeks). DNA content measurement combined with the simultaneous analysis of cell cycle live imaging of fluorescent reporters allowed us to accurately detect cell cycle events in vivo . This technology can distinguish between proliferating cells (diploids in G2/M with 4C DNA content), which express mVenus protein, and polyploid cells having a DNA content ≥ 4C, which express mCherry protein (stationary in G1). We further measured the ploidy of TEC by quantifying the fluorescence of DNA content with a 3D analysis by confocal microscopy. RESULTS: Mice showed an age-related decline of renal function and developed tubulointerstitial fibrosis acquiring a marked senescent phenotype. These structural changes were accompanied by a decrease in the number of RPC (Pax2 + cells) which reside scattered within specific segments of the nephron (S3 segments of the proximal tubule and thick ascending limb of loop of Henle) in the outer stripe of the outer medulla. Importantly, clone frequency analysis revealed that single colored clones consisting of two or more cells increased in mice between 20 and 44 weeks of age and decreased at 80 weeks, suggesting that their proliferative capacity sustains physiologic turnover in young mice, but it is progressively lost during aging. Concurrent to this phenomenon, we observed a significant increase in the percentage of polyploid TEC with 4C or more DNA content during aging, suggesting a role to support augmented functional demand. Conclusions: Collectively, these data suggest that (i) RPC proliferation sustains physiologic renal turnover in kidney, but this capacity is progressively lost during aging. (ii) Polyploidization of TEC gradually increases likely contributing to the physiologic adaption taking place during aging.